Merry Go Round Technique and Students’ Physics Cognitive Learning Outcomes on Work and Energy Topic (Jurnal Pendidikan IPA Indonesia, 2021)
This study aims to determine the difference in learning outcomes in work and energy from students who learned using inquiry training model with merry-go-round techniques. This study was designed using a quasi-experimental design with 74 students as samples. The instrument developed was 21 questions about work and energy. The results show that the experimental class has the highest value of 85.27 compared to the control class with 77.56. The test results of the physics learning outcomes hypothesis were tcount (3,295) ttable (1,666), indicating that there were differences in physics learning outcomes of students who studied using the inquiry training model with the merry-go-round technique than students who studied conventionally.